Evaluation of Thyroid Function Status in Sonographically Suggested Fatty Liver Subjects - Rahman, Farhana; Hossain, Sanowar; Biswas, Shankar Kumar; Haque, Fatema Sultana; Begum, Rubina; Hossain, Mohona; Hossain, Sadia (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: The liver metabolizes thyroid hormones and thereby influences the regulation of their systematic endocrine effects. On the other hand, thyroid hormones play an important role in hepatic lipid homeostasis. Several studies addressed the association between thyroid function tests and non alcoholic fatty liver disease. The results of those studies indicate that hypothyroidism might be related to non alcoholic fatty liver disease. The recognized link between hypothyroidism and elements of metabolic syndrome may explain this relation. The present study was performed to evaluate the thyroid function status with the severity of sonographically suggested fatty liver subjects. Materials and Methods: This cross sectional study was carried out at the Institute of Nuclear Medicine and Allied Sciences (INMAS) of Dhaka Medical College Hospital Campus, Dhaka during the period of January 2014 to December 2014. A total number of 155 consecutive patients having sonographically detected fatty liver from the above mentioned hospitals were included in this study and they were divided into three grades depending on the sonographic criteria. Data were analyzed between these three grades in respect of age, sex, BMI, thyroid hormone levels (FT3, FT4 and TSH), fasting lipid profile and serum liver enzyme levels. Results: 82 (52.9%) patients had grade 1, 50 (32.3%) had grade 2 and 23 (14.8%) had grade 3 fatty liver. The mean age was found 39±10.9 years in Grade 1, 39.5±10.4 years in Grade 2 and 41.4±7.1 years in Grade 3. The difference was not statistically significant (p>0.05) among three groups. Male to female ratio was almost 2:3 in the whole study subjects. The mean BMI was significantly higher in grade 3 (p<0.05) followed by grade 2 and grade 1. 128 (82.6%) patients were euthyroid, 23 (14.8%) were subclinical hypothyroid and 4 (2.6%) were hypothyroid. In Anova test, the mean FT3 and FT4 were significantly declined (p<0.05) with increased grade but the mean TSH level was significantly increased (p=0.001) with increased grade of fatty liver. The Spearman’s rank correlation test shows that no significant but a negative correlation (r= -0.101; p=0.175) was found between FT3 and fatty liver of the study patients, but a significant negative correlation (r=-0.277; p=0.001) was observed between FT4 and fatty liver of the study patients. On the other hand a significant positive correlation (r=0.325; p=0.001) was observed between TSH and fatty liver of the study patients. Conclusion: In this study it has been found that thyroid hormone levels are significantly decreased with increasing grades of fatty liver detected by ultrasound. The underlying pathophysiology for this association is still not clear, however several mechanisms have been proposed. So the findings of this study will inspire other researchers to evaluate the thyroid function status with the severity of sonographically suggested fatty liver in larger scale. Bangladesh J. Nuclear Med. 18(2): 125-130, July 2015